EDUARDO LOURENÇO E AS LABIRÍNTICAS RELAÇÕES BRASIL-PORTUGAL - Soares, Maria de Lourdes (Revista Letras, 2003)
Este texto procura estudar as relações luso-brasileiras ou não-relações, na perspectiva de Eduardo Lourenço. A dissimetria entre os discursos culturais dos dois países. Brasil: o recalque da raiz lusitana, o tempo colonial e o tempo brasileiro. Portugal: o mito da comunidade luso-brasileira, o discurso onírico, o olhar superlativo. Alguns desencontros: ressentimento e delírio; uma língua, dois discursos; um sonho falso, um único sonhador. Perspectivas de futuros encontros. Abstract The relationship between Brazil and Portugal or even its absence, in Eduardo Lourenços opinion. The dissymmetry between the cultural speeches of both countries. Brazil: the sorrow of the Portuguese heritage, the colonial time and the Brazilian time. Portugal: the Portuguese and Brazilian community myth, the dreamful speech, the superlative look. Some divergences: resentment and delirium, one language, two speeches, a false dream, a single dreamer. The perspective of future convergence.